Role of surgery in localized initially unresectable neuroblastoma. Issue 3 (June 2018) - Ahmed, Gehad; Fawzy, Mohamed; Elmenawi, Salma; Elzomor, Hossam; Yosif, Yasser; Elkinaai, Naglaa; Refaat, Amal; Hegazy, Mohamed; El Shafiey, Maged
Summary: Purpose: Evaluating the role of surgery and the extent of tumor resection on the outcome of patients with localized initially unresectable neuroblastoma (NB). Patients and methods: This was a retrospective case review study including patients with localized initially unresectable NB. The primary tumor was considered unresectable according to imaging defined risk factors (IDRFs). Surgical resection was attempted after four to six courses of chemotherapy. The extent of resection was classified as follows: ≥90% resection, incomplete resection (50–90%) and cases with <50% resection or just a biopsy. Survival analysis was performed using an intention-to-treat approach. Results: A total of 202 patients with NB were included. Surgical resection was done in 106 patients. It was ≥90% in 89 patients (83.9%). Surgical resection was not performed in 96 patients (47.5%). Fifty-five (57.2%) were in good response after primary chemotherapy and 41 patients (42.7%) had persisting IDRFs, nine of them had biopsy only, and a follow-up strategy was considered in the other 32 patients. The overall 5-year event-free survival (EFS) and overall survival (OS) were 89.1 ± 2.4% and 94.9 ± 1.7%, respectively, with significantly better OS and EFS for patients who had resection versus no resection ( p  = 0.003 and 0.04, respectively). There was no impact of extent of resection on EFS and OS in the whole group ( p  = 0.91, p  = 0.9) and in subgroup analysis stratified by site, histology, and age of the patients. Conclusion: In children with localized initially unresectable NB, surgical resection was the only significant risk factor associated with better survival. The extent of tumor resection had no impact on EFS and OS. The concept of accepting incomplete resection to avoid serious complications was successful.